Predicting Customer Sentiment in Social Media Interactions: Analyzing Amazon Help Twitter Conversations Using Machine Learning - Arif, Md; Hasan, Mehedi; Al Shiam, Sarder Abdulla; Ahmed, Md Parvez; Tusher, Mazharul Islam; Hossan, Md Zikar; Uddin, Aftab; Devi, Suniti; Rahman, Md Habibur; Ali Biswas, Md Zinnat; Imam, Touhid (SOTVI, 2024)
Social media platforms, particularly Twitter, have become essential sources of data for various applications, including marketing and customer service. This study focuses on analyzing customer interactions with Amazon's official support account,